PENGARUH KEBIJAKAN INSENTIF PAJAK, PENERAPAN E-FORM DAN PEMAHAMAN AKUNTANSI TERHADAP KEPATUHAN WAJIB PAJAK BADAN YANG TERDAFTAR DI KPP PRATAMA, YOGYAKARTA - Ulanda, Marzalita Sopa; Maryani, Dwi; Mintarsih, Ratna Ambar (PRIMA EKONOMIKA, 2023)
This study aims to empirically examine the significant effect of Tax Incentive Policy, E-Form Implementation and Accounting Understanding on Corporate Taxpayer Compliance registered at KPP Pratama, Yogyakarta. The population in this study are corporate taxpayers with normal status registered at KPP Pratama Yogyakarta. Determination of the sample is done by simple random sampling method. The number of samples in this study were 99 taxpayers. The data used in this study is primary data using a questionnaire as a research tool which is distributed directly to respondents or g-form with the link https://bit.ly/KUESIONERSOPA. To determine the magnitude of the relationship of the independent variable to the dependent variable, Multiple Linear Regression analysis was used as a research method with SPSS version 22. The results of this study indicate that the Tax Incentive Policy has no significant effect on Taxpayer Compliance with a significant value of 0.652 > 0.05. Form has a significant effect on Taxpayer Compliance with a significant value of 0.001 <0.05 and Accounting Understanding has a significant effect on Taxpayer Compliance with a significant value of 0.000 <0.05. Meanwhile, simultaneously, Tax Incentive Policy, E-Form Implementation and Accounting Understanding together have a significant effect on Corporate Taxpayer Compliance with a significant value of 0.000 <0.05. The result of the coefficient of determination (R2) shows a value of 0.371, meaning that the variables of Tax Incentive Policy, E-Form Implementation and Accounting Understanding simultaneously affect the Taxpayer Compliance variable by 37.1%. While the remaining 63.9% is influenced by other variables outside this regression equation or variables that are not examined. Keywords : Tax Incentive Policy, E-Form Implementation, Accounting Understanding, Corporate Taxpayer Compliance